1994
DOI: 10.1111/j.1432-1033.1994.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of Yeast Gluconeogenic mRNAs Respond to Environmental Factors

Abstract: The FBPl and PCKl genes encode the gluconeogenic enzymes fructose-l,6-bisphosphatase and phosphoenoZpyruv9te carboxykinase, respectively. In the yeast, Saccharomyces cerevisiae, the corresponding mRNAs are present at low levels during growth on glucose, but are present at elevated levels during growth on gluconeogenic carbon sources. We demonstrate that the levels of the FBPl and PCKl mRNAs are acutely sensitive to the addition of glucose to the medium and that the levels of these mRNAs decrease rapidly when g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 43 publications
6
56
0
1
Order By: Relevance
“…Both, FBP1 and PCK1, are among multiple genes in S. cerevisiae known to be regulated in a carbon source-dependent manner (Roberts and Hudson, 2006;Schüller, 2003;Turcotte et al, 2010). Consistently with published data (Mercado et al, 1994), in a wild-type yeast strain expression of FBP1 and PCK1 was completely repressed when cells were grown in glucose-rich medium but was significantly higher when the cells were grown in a medium with glycerol as shown by Northern blot analysis (Fig. 1).…”
Section: Identification Of Pol II Genes Differentially Expressed In Ssupporting
confidence: 88%
“…Both, FBP1 and PCK1, are among multiple genes in S. cerevisiae known to be regulated in a carbon source-dependent manner (Roberts and Hudson, 2006;Schüller, 2003;Turcotte et al, 2010). Consistently with published data (Mercado et al, 1994), in a wild-type yeast strain expression of FBP1 and PCK1 was completely repressed when cells were grown in glucose-rich medium but was significantly higher when the cells were grown in a medium with glycerol as shown by Northern blot analysis (Fig. 1).…”
Section: Identification Of Pol II Genes Differentially Expressed In Ssupporting
confidence: 88%
“…Snf1, together with the cyclic AMP (cAMP)-dependent protein kinase A (PKA) and target of rapamycin (TOR) pathways, coordinates many of the nutrientresponsive metabolic pathways in yeast (10). Despite the preponderance of evidence indicating altered transcription as the major factor determining the increase in mRNA abundance when yeast cells are depleted of glucose, there is considerable evidence indicating that posttranscriptional changes, particularly an increase in mRNA stability, are also important in determining gene expression levels (11)(12)(13)(14)(15). A recent study demonstrated that promoter sequences influence the subcellular location and efficiency of translation of transcripts upregulated by glucose starvation (16).…”
Section: T He Regulation Of Gene Expression By Nutritional Conditions Inmentioning
confidence: 99%
“…Evidence derived from yeast nuclear genes encoding mitochondrial proteins, particularly SDH1 and SDH2 (17), suggested that this was an example of posttranscriptional regulation of gene expression (18). This is a general process affecting mRNAs encoding gluconeogenic and glyoxylate enzymes (12), enzymes required for the metabolism of nonfermentable carbon sources (19), alternative sugars like maltose (20), galactose (14), and sucrose (21), enzymes of ␤-oxidation and peroxisome biogenesis, and transporters of amino acids and alternative carbon sources like lactate (19,22). Regulation of the process may involve multiple signaling pathways, because different genes are affected at different glucose concentrations.…”
Section: T He Regulation Of Gene Expression By Nutritional Conditions Inmentioning
confidence: 99%
“…Addition of a fermentable carbon source to cells growing oxidatively leads to the rapid decay of transcripts derived from the glucose-repressible genes CYC1 (56), SUC2, SDH1, SDH2 (50,(57)(58)(59)(60), FBP1, PCK1 (49,61), and JEN1 (48). In addition GAL mRNAs respond to a shift from galactose-to-glucose metabolism by a dramatic shortening of their half-lives (2,62).…”
Section: Snf1 May Inhibit Transcription At Amentioning
confidence: 99%